The Performance of Aluminium Dust as Sand Replacement in Concrete Mixture in term of Compressive Strength and Water Absorption - LEE, BRYAN IIAN; Ahmad Jeni, Mohamad Luthfi Bin (Progress in Engineering Application and Technology, 2025)
The objectives goal from this research are as follows is to examine the feasibility of using aluminum dust as a potential sustainable source of natural sand for concrete production in order to address environmental issues resulting from sand exhaustion in construction industry. The research examines the impact of different proportion of aluminum dust in 30 cubes of sample concrete gotten from industries in Sandakan, Sabah, including its mechanical characteristics which are water absorption, durability, compressive strength, and workability at percentage concentration of 5%, 10%, 15%, and 20%. Hence, the preliminary study offers benefits of lowering permeability and enhancing resistance to these impacts. Aluminum dust concrete has provided the concrete with increased durability, reduced density and increased compressive strength. Furthermore, with electrostatic repulsion and the incorporation of [Al(OH)4] into the silica matrix, the alkali-silica reaction (ASR) could also be decreased by the chemical characteristics of the aluminum waste. Besides explaining why it can prolong the setting times and also has high pozzolanic activity, its high silicate, oxide, and carbon content also improve mechanical properties and water resistance. Therefore, while analysing the drawbacks such as constant properties, reaction with cementing materials and others of this work prove that aluminium dust has the features of a sustainable material in construction that can minimize the pollution of the environment, rational usage of resources and contributed to the development of ecological construction.